2010
DOI: 10.3386/w15801
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary Unemployment and the Business Cycle

Abstract: 4Non-technical summary 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 2 publications
4
27
0
Order By: Relevance
“…The autocorrelation of the taste shock ' t ; which distinguishes it from the i:i:d: wage markup shock w;t , re ‡ects the prior view that taste shocks are a more plausible device to capture the e¤ects on hours worked of changes in labor force 2 Galí (2010) and Gali, Smets, and Wouters (2011) propose a reinterpretation of this same model with an explicit treatment of unemployment, in which the two shocks can be separately identi…ed. For a DSGE model with similar implications, but alternative microfoundations of unemployment, see Christiano, Trabandt, and Walentin (2010). participation and other low-frequency movements largely unrelated to the business cycle, but are nonetheless evident in our data.…”
Section: The Model Economymentioning
confidence: 71%
See 1 more Smart Citation
“…The autocorrelation of the taste shock ' t ; which distinguishes it from the i:i:d: wage markup shock w;t , re ‡ects the prior view that taste shocks are a more plausible device to capture the e¤ects on hours worked of changes in labor force 2 Galí (2010) and Gali, Smets, and Wouters (2011) propose a reinterpretation of this same model with an explicit treatment of unemployment, in which the two shocks can be separately identi…ed. For a DSGE model with similar implications, but alternative microfoundations of unemployment, see Christiano, Trabandt, and Walentin (2010). participation and other low-frequency movements largely unrelated to the business cycle, but are nonetheless evident in our data.…”
Section: The Model Economymentioning
confidence: 71%
“…Gali, Smets, andWouters (2011) andChristiano, Trabandt, andWalentin (2010)). One consequence of this …nding is that medium scale New-Keynesian models like the one presented here might be more useful for policy analysis than suggested for instance by Chari, Kehoe, and McGrattan (2009).…”
Section: The Interpretation Of Labor Supply Shocksmentioning
confidence: 99%
“…Extensively studied in the literature is the role of search and matching frictions, along with frameworks such as the involuntary unemployment framework of Christiano et al. (), the rigid‐wage class of models as in Gali () and Gali et al. (), as well as earlier versions of the labor selection model incorporating New Keynesian pricing frictions and wage‐setting frictions, such as Lechthaler et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2010) found that the risk of unemployment negatively a¤ects utility of employed workers: An increases in aggregate unemployment decreases workers'subjective wellbeing, which can be explained by an increased risk of becoming unemployed. I take account of this e¤ect in an otherwise standard New Keynesian open economy model with unemployment as in Galí (2010) and …nd two important results with respect to expansionary monetary policy shocks: First, the usual wealth e¤ect in New Keynesian models of a declining labor force, which is at odds with the data as highlighted by Christiano, Trabandt and Walentin (2010), is shut down. Second, the welfare e¤ects of such shocks improve considerably, modifying the standard results of the open economy literature that set o¤ with Obstfeld and Rogo¤'s (1995) redux model.…”
Section: Standard-nutzungsbedingungenmentioning
confidence: 71%
“…There it is consumption temporarily growing faster than trend in a boom that induces a lower disutility from work. 5 As consumption growth will be strong when unemployment is low, the underlying mechanism is indeed similar. 6 The consumption index C t is de…ned as…”
Section: Preferences and Goods Demandmentioning
confidence: 99%